PENERAPAN MODEL KOOPERATIF TIPE ROUNDTABLE DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS X SMA - Triwahyu Puspa Huda (Riksa Bahasa, 2016)
The purpose of this study was to describe the activities of students in learning writing exposition text by using the model and the type cooperative roundtable determine the effectiveness of roundtable type of cooperative models in the teaching of writing text exposition in class X SMA. This roundtable type of cooperative models applied in teaching writing text exposition. This model is a technique of learning to write by each student writes down ideas in turns to form a round table. The method used in this research is quantitative research (quasi). Data were collected by direct observation and analysis of documents. The results showed that students apply the model of cooperative roundtable active in expressing ideas to be developed into a text exposition. The activity seen from the direct interaction between members and a sense of cooperation for mutual support and accept the idea. Percentage obtained reached 94.87% with the criteria very well. Based on statistical calculations t-test, the results t hitung reached 1.70 while ttabel with degrees of freedom (df) 35 and a significance level of 0.05 was obtained a value of 1.69. That is, t count greater than t table (t count 1.70 t tabel 1.69). Thus, it can be defined model of cooperative roundtable effective in enhancing the ability to write text exposition in class X SMAN 7 Cirebon.